Effect of dopants on electrical properties of BCT-BZT lead free piezo ceramics: a review. Issue 1 (22nd October 2021) - Sahoo, B.; Thejas, T. S.; Politova, E. D.; Panda, P. K.
Abstract: Lead free piezo materials are becoming popular as the world is conscious about toxicity of PbO present in PZT. As a result, lot of R&D efforts are made in last two decades to find out suitable lead free piezo ceramics as effective as PZT. There are many lead free piezo systems explored. Among them, BZT-BCT is more promising due to its high piezoelectric coefficients. This system is well researched by modifying its structure with a large number of dopants. In this paper, an effort has been made to review the effect of various dopants on electrical properties of BCT-BZT systems.